2018
DOI: 10.3329/jbau.v16i2.37981
|View full text |Cite
|
Sign up to set email alerts
|

Water supplementation of Moringa oleifera as a substitute for antibiotics on performance and blood parameters of broiler chickens

Abstract: There is a serious public health concern of the use of antibiotics sub-therapeutically and/or as growth promoter in poultry feed and water. Therefore, there is an urgent need for alternatives. Moringa oleifera is a phytobiotic, which has been reported to possess antimicrobial and immuno-modulatory properties. This study aimed to investigate the effects of aqueous M. oleifera leaf extract (MOLE) supplementation on growth performance and hematological indices of broiler chickens. The 36 day-old broiler chicks (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
4
2
Order By: Relevance
“…There were no significant differences on FCR (TABLE V), results that differ from those of Paul et al [16], who included 1% of the aqueous extract of M. oleifera in the drinking water of Cobb 500 B for 5 wk and whose results showed a lower FCR when compared to the control group. On the other hand, the present results were similar to what was found in the study by Mesa et al [14], who included 0.10, 15 and 20% of M. oleifera forage meal in the feed of White Leghorn L33 laying hens from 19 to 26 wk of age, and did not show any difference in FCR.…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 75%
“…There were no significant differences on FCR (TABLE V), results that differ from those of Paul et al [16], who included 1% of the aqueous extract of M. oleifera in the drinking water of Cobb 500 B for 5 wk and whose results showed a lower FCR when compared to the control group. On the other hand, the present results were similar to what was found in the study by Mesa et al [14], who included 0.10, 15 and 20% of M. oleifera forage meal in the feed of White Leghorn L33 laying hens from 19 to 26 wk of age, and did not show any difference in FCR.…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 75%
“…The birds which were fed diets with 750 g/100 kg of Moringa leaf meal had the greatest feed-conversion ratio (FCR), which fell as the amount of Moringa leaf meal in the diet decreased. Paul et al [ 75 ] concluded that the aqueous extract of the M. oleifera leaves reduced feed intake and enhanced the FCR in comparison with antibiotics in broiler chickens. According to El-Tazi et al [ 61 ], using 5% Moringa meal in the broiler diet boosted the feed intake and feed-conversion ratio considerably.…”
Section: Feed Intake and Efficiencymentioning
confidence: 99%
“…Generally, the MO leaves has anti-tumor and antinflammatory properties (Paul et al, 2018). Concerning the observed improvement in immunity of rabbits treated with MODLP, similar results were reported on growing rabbits fed MO leaf meal under moderate heat stress (El-Gindy et al, 2017), broilers fed MO leaves (Olugbemi et al, 2010) and mice orally treated with MO leaves methanolic extract (Sudha et al, 2010).…”
Section: Antioxidant and Immunitymentioning
confidence: 53%
“…Therefore, MO leaves have ability to affect oxidative damage in animals by increasing anti-oxidant enzymes activity, decreasing lipid peroxidation, free radicals generation, and suppression of ROS formation (Osman et al, 2012), consequently improving meat quality (Giannenas et al, 2010). The MO leaves has properties as anti-tumor, antinflammatory, anti-oxidant, anti-ulcerous, antihyperlipidaemic and cholesterol lowering, anti-diabetic, anti-cancereous (Paul et al, 2018), anti-fungal and anti-bacterial (Bukar et al, 2010), which include 4-("-L-rhamnopyranosyloxy) benzyl isothiocyanate, Niazimicin, Pterygospermin, Benzyl isothiocyanate, 4-("-Lrhamnopyranosyloxy) and Benzyl glucosinolate (El-Kholy et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation